An Improved Effective Cost Review Process for Value Engineering - D. S. Joo; J. I. Park (The Scientific World Journal)
Second-look value engineering (VE) is an approach that aims to lower the costs of products for which target costs are not being met during the production stage. Participants in second-look VE typically come up with a variety of ideas for cost cutting, but the outcomes often depend on their levels of experience, and not many good alternatives are available during the production stage. Nonetheless, good ideas have been consistently generated by VE experts. This paper investigates past second-look VE cases and the thinking processes of VE experts and proposes a cost review process as a systematic means of investigating cost-cutting ideas. This cost review process includes the use of an idea checklist and a specification review process. In addition to presenting the process, this paper reports on its feasibility, based on its introduction into a VE training course as part of a pilot study. The results indicate that the cost review process is effective in generating ideas for later analysis.